2018
DOI: 10.1007/s10658-018-1469-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Lycium europaeum extracts on phytopathogenic soil-borne fungi and the reduction of late wilt in maize

Abstract: The ability to control soil-borne pathogens is mainly conditioned by the restrictions to the use of synthetic pesticides, and genetic resistance is hindered by new pathogen races or by only a partial expression of the resistance. Allelopathy, the antimicrobial activity of plant extracts, is a promising option against crop pathogens. Extracts from some Lycium spp. possess biological and therapeutic properties. Individual methanolic extracts from L. europaeum were each evaluated in vitro against Verticillium dah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…effect on organisms at different levels. The effect of these extracts depends on fungal species (Tej et al, 2018). In the case of fungi, the effect may be inhibition of mycelial growth or spore germination (Juvaddi et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…effect on organisms at different levels. The effect of these extracts depends on fungal species (Tej et al, 2018). In the case of fungi, the effect may be inhibition of mycelial growth or spore germination (Juvaddi et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the antimicrobial activity of plant extracts and plant-derived compounds has accumulated over the last decade. In vitro experiments by our research group have shown the antifungal activity of Lycium europaeum extracts on the sunflower pathogens V. dahliae and Sclerotinia sclerotiorum, and even their effect against in reducing late wilt of maize was observed (Tej et al, 2018). Extracts of L. europaeum reduced the mycelial growth of both fungi and smaller numbers of sclerotia of S. sclerotiorum were formed.…”
Section: Entomopathogenic Fungimentioning
confidence: 97%
“…The consistency of biological control on a field scale has not been demonstrated (El-Mehalawy et al, 2004;Bergstrom et al, 2008). Similarly, the bioactivity of Lycium europaeum extracts through direct inhibition of both growth and sporulation of the pathogen, as well as by a reduction in disease development, has recently been reported, but under greenhouse conditions (Tej et al, 2018).…”
Section: Introductionmentioning
confidence: 94%